Doppler ultrasonography of the anterior knee tendons in elite badminton players: colour fraction before and after match. Issue 2 (1st April 2008) - Koenig, M J; Torp-Pedersen, S; Boesen, M I; Holm, C C; Bliddal, H
Abstract : Background: Anterior knee tendon problems are seldom reported in badminton players although the game is obviously stressful to the lower extremities. Hypotheses: Painful anterior knee tendons are common among elite badminton players. The anterior knee tendons exhibit colour Doppler activity. This activity increases after a match. Painful tendons have more Doppler activity than tendons without pain. Study design: Cohort study. Methods: 72 elite badminton players were interviewed about training, pain and injuries. The participants were scanned with high-end ultrasound equipment. Colour Doppler was used to examine the tendons of 64 players before a match and 46 players after a match. Intratendinous colour Doppler flow was measured as colour fraction (CF). The tendon complex was divided into three loci: the quadriceps tendon, the proximal patellar tendon and the insertion on the tibial tuberosity. Results: Interview: Of the 72 players, 62 players had problems with 86 tendons in the lower extremity. Of these 86 tendons, 48 were the anterior knee tendons. Ultrasound: At baseline, the majority of players (87%) had colour Doppler flow in at least one scanning position. After a match, the percentage of the knee complexes involved did not change. CF increased significantly in the dominant leg at the tibial tuberosity; single players had a significantly higher CF after a match at the tibial tuberosity and in the patellar tendon both before and after a match. Painful tendons had the highest colour Doppler activity. Conclusions: Most elite badminton players had pain in the anterior knee tendons and intratendinous Doppler activity both before and after match. High levels of Doppler activity were associated with self-reported ongoing pain.